Different, different but same? Recreational opportunities and user preferences of inner-city Urban Green Spaces in Hanover and Thessaloniki - Ingmann, Karlotta; Katsavounidou, Garyfallia; Mehnen, Nora (Frontiers in Sustainable Cities, 2025)
Studies on Urban Green Spaces (UGSs) often focus on quantity and/or proximity but lack qualitative assessment, which is particularly important in the case of cross-regional comparisons. This paper comparatively examines the quality of UGSs in Hanover (Germany) and in Thessaloniki (Greece) considering their contrasting characteristics, layouts, climate, and culture. Using a combination of tools including multi-dimensional mapping, direct observation, and user survey, 20 inner-city green spaces in Hanover and Thessaloniki were assessed and analysed in a previous study. Based on these results, this paper focuses on the two most popular UGSs from each city: Maschpark and Alexander the Great Garden, respectively. Distinct differences exist in terms of their structural diversity, with Maschpark prioritising biotic factors, while in Alexander the Great Garden infrastructure and abiotic factors are prevalent. In both UGSs a high number and a wide range of recreational activities were observed. Survey showed that presence of greenery and biotic elements primarily influence users’ satisfaction in Maschpark, while in Alexander the Great Garden, cultural significance and location on the waterfront contribute to its popularity. This study highlights the value of cross-regional comparison of UGSs to better understand which design factors contribute to their quality and enhance user satisfaction. Despite the differences of the urban landscape between Greek and German cities, notably in terms of green area per capita, results revealed that people’s use of UGSs have more in common than stereotypically implied and that users’ needs are to a great extent cross-cultural.